1997
DOI: 10.1007/s002040050459
|View full text |Cite
|
Sign up to set email alerts
|

Cardiotoxicity of chlorodibromomethane and trichloromethane in rats and isolated rat cardiac myocytes

Abstract: The cardiovascular effects were investigated after acute and subacute treatment with chlorodibromomethane (CDBM; 0.4 to 3.2 mmol/kg p.o.), trichloromethane (TCM; 0.31 and 1.25 mmol/kg p.o.) and mixtures of CDBM and TCM (acute, 0.8 mmol CDBM/kg + 1.25 mmol TCM/kg p.o.; subacute, 0.4 mmol CDBM/kg + 0.31 mmol TCM/kg p.o.) in conscious and urethane anaesthetized male Wistar rats (n = 6-10 per treatment). Furthermore it was observed whether cardiovascular responses were modified in CDBM or TCM treated rats after ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 33 publications
0
2
1
Order By: Relevance
“…This study, to our knowledge, is the first to explore the association between THM exposure and total, all-cause, and cardiovascular mortality. While some in vivo and in vitro evidence has supported the cardiac toxicity of THMs, 21 we did not find any convincing associations between blood THMs exposure and heart disease mortality, which might be due to the difference in species susceptibility and/or exposure levels tested in laboratory animals compared with those normally found in humans. 52 Instead, we found a relationship between elevated blood TCM and TTHM concentrations and a greater risk of all-cause and cancer mortality risk.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…This study, to our knowledge, is the first to explore the association between THM exposure and total, all-cause, and cardiovascular mortality. While some in vivo and in vitro evidence has supported the cardiac toxicity of THMs, 21 we did not find any convincing associations between blood THMs exposure and heart disease mortality, which might be due to the difference in species susceptibility and/or exposure levels tested in laboratory animals compared with those normally found in humans. 52 Instead, we found a relationship between elevated blood TCM and TTHM concentrations and a greater risk of all-cause and cancer mortality risk.…”
Section: Discussioncontrasting
confidence: 98%
“…In an early study, Min and colleagues found that higher blood concentrations of BDCM, DBCM, TBM, and total brominated THMs (Br-THMs; sum of BDCM, DBCM, and TBM) were associated with a higher risk of overall cancer mortality among 933 U.S. adults aged 40–59 years from the National Health and Nutrition Examination Survey (NHANES) 1999–2004 . Further evidence shows associations of THM exposure with cardiac and hepatic toxicity, type 2 diabetes, , as well as adverse reproductive outcomes (e.g., pregnancy loss), suggesting a potential association of THM exposure with noncancer mortality. However, no studies to date have examined associations between THM exposure with all-cause and other non-cancer-related mortality. Therefore, we performed the present analysis by including more recent NHANES data with four additional survey cycles (1999–2012 vs 1999–2004) and seven times the number of participants (6720 vs 933) relative to the study conducted by Min and colleagues, exploring the relationship between blood THM concentrations and mortality due to all causes, heart diseases, cancer, and any other causes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to arrhythmias, halogenated hydrocarbons have negative inotropic, dromotropic, and chronotropic effects on cardiac tissue [73]. Cases of atrioventricular conduction abnormality have been described in toluene intoxication [74].…”
Section: Inhalent Abusementioning
confidence: 99%